2018
DOI: 10.20344/amp.10395
|View full text |Cite
|
Sign up to set email alerts
|

Biópsia do Gânglio Sentinela Guiada por Fluorescência no Cancro da Mama: Taxa de Deteção e Performance Diagnóstica

Abstract: Introduction: Sentinel lymph node biopsy is currently the standard surgical procedure for lymph node staging in patients with early stage breast cancer. It is performed using different techniques, such as the injection of vital dyes and / or radioisotopes and, more recently, guided by fluorescence using Indocyanine green. The aim of this study is to assess the detection rate of sentinel lymph node using Indocyanine green in breast cancer patients according to factors related to the patient and the tumor.Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…On the contrary to the above studies, a prospective trial from the UK that enrolled all SLNB eligible breast cancer patients who underwent combined ICG + BD-guided SLNB found that ICG is effective irrespective of the patients BMI [21]. Finally, the retrospective study by Vaz et al on the combined triple use of ICG + RI + BD for SLNB reported that there was no statistically significant difference regarding the performance of either of the three methods in comparison with the patient's BMI [48].…”
Section: Icg As Slnb Tracer In Obese Patientsmentioning
confidence: 91%
See 1 more Smart Citation
“…On the contrary to the above studies, a prospective trial from the UK that enrolled all SLNB eligible breast cancer patients who underwent combined ICG + BD-guided SLNB found that ICG is effective irrespective of the patients BMI [21]. Finally, the retrospective study by Vaz et al on the combined triple use of ICG + RI + BD for SLNB reported that there was no statistically significant difference regarding the performance of either of the three methods in comparison with the patient's BMI [48].…”
Section: Icg As Slnb Tracer In Obese Patientsmentioning
confidence: 91%
“…Several single-group studies examined the effectiveness of ICG as SLNB tracer, by evaluating the clinical data of patients that have undergone SLNB directed by all three tracers, ICG + BD + RI. These studies reported an IRs of 91.4% to 96% for the use of ICG [47][48][49][50]. Furthermore, Somashekhar et al who analyzed the data of 100 clinically node-negative breast cancer patients who received ICG + BD + RI guided SLNB, concluded that the detection rate of ICG was 96%, not significantly different than the IR = 94% for the dual BD + RI method.…”
Section: Studies Using Icg Ri and Bd As Slnb Tracersmentioning
confidence: 98%
“…O LS é definido como o primeiro linfonodo da cadeia linfática que recebe a drenagem do tumor (Silva et al, 2021). A detecção do LS tem a finalidade de prever a condição linfonodal, evitando assim o esvaziamento ganglionar nos pacientes que não tenham comprometimento metastático (Vaz;Peleteiro, 2018). A cirurgia é pequena e menos agressiva, removendo apenas os linfonodos identificados pelo método, já que o esvaziamento linfonodal pode trazer contrariedades importantes como seromas, hematomas, linfedema, sensibilidade local, dor, alterações de movimento relacionada ao membro e internações (Oliveira;Lima;Carvalho, 2018).…”
Section: Introductionunclassified